1996
DOI: 10.1002/star.19960481113
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Simulation of a Simulated‐Moving‐Bed Chromatographic Reactor for the Inversion of Sucrose

Abstract: Bibliography[l] Sanders, P., and K . Brunr: Improved method for the determination of the total adipyl content in acetylated adipyl cross-linked starches. StarchIStarke 46 (1994), 255-259. Gunten, D. von, and D. Korduba: Determination of free adipic acid in acetylated di-starch adipate products. Circular letter STEX 13/84, June ZOth, 1984.[3] Whitehouse, D. B.: Starch -Determination of the total adipate content and the free adipic acid content in adipate crossbonded [2] starches (first draft). ISO/TC 93 WG2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…23 Several liquid-phase SMBR applications are found in the literature. Examples of biochemical reactions are the isomerization of glucose with glucose isomerase, [24][25][26][27] the inversion of sucrose by action of invertase, 28,29 and the production of lactosucrose by action of b-fructofuranosidase. 30 Examples of reversible chemical reactions catalyzed by ion-exchange resins are the esterification of acetic acid with b-phenetyl alcohol, 31 the ethyl acetate synthesis on Amberlyst ® 15, 9,32 the synthesis of bisphenol A from acetone and phenol, 33 esterification of acetic acid with methanol, 34 and synthesis of MTBE.…”
Section: Figure 2 Simulated Moving-bed Reactormentioning
confidence: 99%
“…23 Several liquid-phase SMBR applications are found in the literature. Examples of biochemical reactions are the isomerization of glucose with glucose isomerase, [24][25][26][27] the inversion of sucrose by action of invertase, 28,29 and the production of lactosucrose by action of b-fructofuranosidase. 30 Examples of reversible chemical reactions catalyzed by ion-exchange resins are the esterification of acetic acid with b-phenetyl alcohol, 31 the ethyl acetate synthesis on Amberlyst ® 15, 9,32 the synthesis of bisphenol A from acetone and phenol, 33 esterification of acetic acid with methanol, 34 and synthesis of MTBE.…”
Section: Figure 2 Simulated Moving-bed Reactormentioning
confidence: 99%
“…In such a case the removal of the inhibitor from the reaction zone results in a higher yield [133,134].…”
Section: Removal Of Inhibitorsmentioning
confidence: 99%
“…The computer calculation takes 1 -2 days on a modern PC. The approach was tested taking the inversion of sucrose into fructose and glucose [134,148] and the production of bphenethyl acetate from acetic acid and b-phenethyl alcohol [161] as examples. The authors concluded that a potential saving in operating cost of up to 20% and reduction of desorbent consumption of up to 60% can be achieved.…”
Section: Simulated Moving Bed Reactors (Smbr)mentioning
confidence: 99%
See 1 more Smart Citation
“…11,14,15 The biochemical reactions involving sugars have been also investigated extensively, as glucose isomerization, [16][17][18][19] inversion of sucrose by enzyme invertase, [20][21][22] production of high molecular weight dextran, 21 enzymatic conversion of glucose to glucose-6-phosphate, 23 hydrolysis of lactose and maltose, 24,25 and the production of lactosucrose. 26 Even though a reasonable amount of experimental and numerical studies on SMBR have been published, there is still no reported application of SMBR in the chemical process industry.…”
Section: Introductionmentioning
confidence: 99%